MADURESE PROVERBS USING COLOR NAME ELEMENT: AN ETHNOLINGUISTIC STUDY - Nurul Fadhilah; Wakit Abdullah Rais; Dwi Purnanto (Humanus: Jurnal Ilmiah Ilmu-ilmu Humaniora, 2019)
Color is a symbolic expression tool used by humans to translate the intentions and ideas of its users, not exception the color names used in proverbs. This research is a qualitative descriptive which aims to describe the meaning of Madurese proverbs which contain color name elements and their relation to the Madurese life principles. The data of this study are Madura proverbs which contain color name elements. Furthermore, primary data sources come from informants and secondary data sources come from books and internet pages. Data were analyzed using an ethnolinguistic approach with ethnoscience methods. The results showed that 6 Madurese proverbs used the color name elements. The colors are potѐ ‘white’, celleng ‘black’, and konѐng ‘yellow’. Each same color can have a different meaning in each proverb. Besides, the six proverbs that use the color name elements become Madurese life guidelines in running their life, such as having to maintain self-esteem, be humble, avoid abuse of power, keep trying, be a person who has good character, and associate with people who bring benefits. Thus, this research is fundamental because the color is not just a symbol of beauty, but it can show the culture of its users in the form of language expression.